Managing vocational training systems : a handbook for senior administrators - Gasskov, Vladimir [Verfasser] (International Labour Office, 2000)
This book "addresses the multiplicity of challenges facing public vocational education and training (VET) programmes around the world. An essential guide for VET administrators, this comprehensive handbook provides state-of-the-art materials and frameworks for co-ordinating important management and structural reforms. It offers practical guidelines for managing budget and finance, evaluating performance, and developing strategic operational plans, along with other valuable methods and techniques for running effective VET systems. Organized into six distinct modules, the volume provides suggestions for identifying and reacting to labour market signals and solving common problems in strategic planning, and offers useful analytical tools for programme assessment. Providing real-life examples of VET management practices, the resource describes a structure of funding mechanisms and reviews schemes for financing vocational education, labour market training and government regulated financing of training in enterprises. It also outlines a key framework for guiding training providers to improve organizational structure, staffing and budgeting procedures, and quality control." (Verlag, BIBB-Doku)
Keywords: S 5.1 Bildungsmanagement; S 2.3 Berufsbildungspolitik; S 4.1 Finanzierungsquellen; L 6.2.3 Evaluation; Berufsbildung; Berufsbildungssystem; Bildungsmanagement; Bildungsplanung; Bildungsverwaltung; Berufsbildungspolitik; Bildungsfinanzierung; Evaluation